(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Teacher-student relationships, especially for elementary, middle, and high school students, are age-appropriate. The complexity of teacher-student relationships varies across classrooms, requiring professional expertise on the part of the teacher. Teachers are not always successful in building trusting relationships with students, and constantly treating them as children creates certain barriers to achieving trusting relationships. Disturbance of relations with teachers can manifest itself in the form of distrust, misunderstanding, injustice, irritability, excessive or insufficient demands, ignoring the opinions of others, unkindness, contradiction between words and actions, deficiencies in teaching.